Case report of a bilateral adrenal myelolipoma associated with Cushing disease. Issue 52 (December 2017) - Park, Se Yoon; Kwak, Mi Kyung; Kim, Hye Jeong; Park, Hyeong Kyu; Suh, Kyo-Il; Yoo, Myung Hi; Jin, So Young; Yun, Sumi; Byun, Dong Won
Abstract: Rationale: Adrenal myelolipomas are rare benign tumors, composed of a variable mixture of mature adipose tissue and hematopoietic tissue. These tumors are frequently detected incidentally and are usually asymptomatic, and hormonally inactive. Patient Concerns: During a routine health checkup, a 52-year-old man was found to have a tumor on the bilateral adrenal glands. Abdominal computed tomography revealed a well-defined, heterogeneously enhanced bilateral adrenal mass, suggesting a myelolipoma. Diagnoses: The hormonal evaluation revealed adrenocorticotropic hormone (ACTH) dependent Cushing syndrome. Interventions: The patient underwent left adrenalectomy, and transsphenoidal resection of a pituitary mass. The final diagnosis was adrenal myelolipoma associated with Cushing disease. Outcomes: Growth of right adrenal myelolipoma was detected during the 7-year follow-up. There were enhancing pituitary lesions in repeat magnetic resonance imaging of the sellar region, which implies persistent or recurrent pituitary adenoma. This case reinforces relationship between Cushing disease and adrenal myelolipoma. Lessons: To the best of our knowledge, this is the first reported pathologically confirmed bilateral adrenal myelolipoma associated with Cushing disease. This report supports the idea that ACTH is associated with the development of adrenal myelolipoma. Abstract : Supplemental Digital Content is available in the text